Predictors of ICU Mortality among Mechanically Ventilated Patients: An Inception Cohort Study from a Tertiary Care Center in Addis Ababa, Ethiopia - Finot Debebe; Alberto Goffi; Tewodros Haile; Fetiya Alferid; Haimanot Estifanos; Neill K. J. Adhikari (Critical Care Research and Practice)
Background. Mechanical ventilation is a life-saving intervention for patients with critical illnesses, yet it is associated with higher mortality in resource-constrained settings. This study intended to determine factors associated with the mortality of mechanically ventilated adult intensive care unit (ICU) patients. Methods. A one-year retrospective inception cohort study was conducted using manual chart review in ICU patients (age >13) admitted to Tikur Anbessa Specialized Hospital (Addis Ababa, Ethiopia) from September 2019 to September 2020; mechanically ventilated patients were followed to hospital discharge. Demographic, clinical, and outcome data were collected; logistic regression was used to determine mortality predictors in the ICU. Result. A total of 160 patients were included; 85/160 (53.1%) were females and the mean (SD) age was 38.9 (16.2) years. The commonest indication for ICU admission was a respiratory problem (n = 97/160, 60.7%). ICU and hospital mortality were 60.7% (n = 97/160) and 63.1% (n = 101/160), respectively. Coma (Glasgow Coma Score <8 or 7 with an endotracheal tube (7T)) (adjusted odds ratio [AOR] 6.3, 95% confidence interval 1.19–33.00), cardiovascular diagnosis (AOR 5.05 [1.80–14.15]), and a very low serum albumin level (<2 g/dl) (AOR 4.9 [1.73–13.93]) were independent predictors of mortality (P<0.05). The most commonly observed complication was ICU acquired infection (n = 48, 30%). Conclusions. ICU mortality in ventilated patients is high. Coma, a very low serum albumin level (<2 g/dl), and cardiovascular diagnosis were independent predictors of mortality. A multifaceted approach focused on developing and implementing context appropriate guidelines and improving skilled healthcare worker availability may prove effective in reducing mortality.